ANALYSIS OF THE ORGANIZATIONAL CULTURE DIMENSIONS IN THE INDONESIAN ANTI-CORRUPTION AGENCY: A CASE STUDY OF KOMISI PEMBERANTASAN KORUPSI - William, Joshua; Hendarman, Achmad Fajar (Journal of Business and Management, 2018)
Abstract. KPK was founded as an independent agency that has the power to both investigate and prosecute cases that involve law enforcement personnel or public officials. Because KPK was established out of the lack of public trust in the existing law enforcement agencies, it is important to keep this new agency free from the malpractice that is rampant in the nation’s civil service system. The need to establish an organizational culture that is based on integrity became critical to ensure that the officers could reject any undue influences and the attempt to clean up the bureaucracy could be made. The study sought to develop a conceptual framework of organizational culture in the law enforcement agencies by identifying the dimensions of the organizational culture in KPK. The methodology used in this study is the qualitative approach with semi-structured interview. The study utilized the data from interviews transcripts to determine the dimensions of the organizational culture of KPK as an anti-corruption agency. The organizational culture dimensions could be developed into research instrument and used by KPK to assess the impact that an organizational culture might have to the staff attitudes, behavior, and performance. Keywords:  Anti-Corruption Agency, KPK, Organizational Culture, Qualitative Study